Master in human talent management. Object of study and justification - Pabón Arévalo, Horacio Leonel (SATHIRI, 2019)
Since today"™s organizations have to move in a dynamic and competitive environment; the people who are part of these constitute the heart of its operating system and, therefore, they must be treated as associates or collaborators of the company and not as mere productive resources. That is the new vision of human resources management. Therefore, it is necessary and urgent to impregnate thisnew vision in organizations. Therefore, the research was aimed at justifying an object of study of a master"™s program with that vision. Such an object is constructed through a bibliographic review and, for the determination of the demand for a master"™s program with an object of study of these characteristics, surveys were applied to two subgroups of subjects, and publications referring to national planning were reviewed and local state agencies of Ecuador. The analysis techniques were descriptive statistics and content analysis. The results support the object of study and the need to respond to a specific problem of human talent management training. Consequently, and with the guidance of the Higher Education Council (CES) for the formulation of postgraduate projects, a master"™s project in human talent management was developed.
Keywords: Human talent management; object of study; Ecuador